The Influence of Leadership Style, Compensation and Motivation on Employee Performance in Vehicle Trader Company - Titin Endrawati; Hartanto; Dedik Wiryawan; Subekti; Helmi Ali (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The primary objective of this investigation is to explore how leadership style, remuneration, and drive affect employee performance. The research was conducted on employees utilizing the convenience sampling method. Multiple regression was utilized as the statistical examination. The study has four core goals: firstly, to examine the influence of leadership style on employee performance; secondly, to assess the impact of remuneration on employee performance; thirdly, to scrutinize the effect of drive on employee performance; and fourthly, to investigate the impact of leadership style, remuneration, and drive on employee performance. The findings of this study indicate that there is a simultaneous effect on the variable on buying decisions. It is apparent that the significant value is less than 0.05, and the f-count value is higher than the f-table. Moreover, the results of this study demonstrate that the t-count value for the leadership style variable, remuneration, and drive is greater than the t-table, indicating that there is an effect on employee performance. The determination test shows that 72% of the independent variables influence the dependent variable, while 28% is influenced by other variables that are not included in this regression analysis, such as organizational culture, skills, job satisfaction, and others.